Water infiltration into the soil – what do measurements indicate? - Orfánus, Tomáš; Nagy, Viliam (Acta Agraria Debreceniensis, 2018)
Physical properties of top-soil organic materials significantly influence initiation processes of infiltration and runoff generation. This paper deals with the specifics of water infiltration through the top surface organic layer of the forest soil. Three field methods (Guelph permeameter, Tension disk permeameter, Single-ring method) and one laboratory method (Falling head) of hydraulic conductivity (KS) determination are compared and interpreted in the context of their applicability and limitations. The Falling head method provides far different values of KS if sample cylinders are or are not sealed with grease against the wall effect. The Guelf permeameter is very significant to the position of different horizons’ interface, while Tension disc permeameter results are dependent on antecedent soil moisture. The single ring method is applicable with acceptable results only when there is no abrupt interface between horizons in the vicinity of the ring bottom edge.